IRON, FOLATE AND COBALAMIN DEFICIENCY IN ANAEMIC PREGNANT FEMALES IN TERTIARY CARE CENTRE AT RAWALPINDI - Khan, Dilshad Ahmed; Fatima, Samia; Imran, Rabia; Khan, Farooq Ahmad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Anaemia in pregnancy is a common clinical problem contributing to increased maternal and foetal morbidity. This study was carried out to determine frequency of iron, folate and cobalamin deficiency and associated risk factors in the anaemic pregnant females who reported first time during second and third trimester for antenatal check-up in the tertiary care hospital at Rawalpindi. Methods: This case control study was carried out in a tertiary care hospital at Rawalpindi. Two hundred and fifty pregnant women (age: 19-43 years) consisting of 125 anaemic (Hb< 110 g/L) and 125 non-anaemic who reported first time at antenatal clinic were included. Data on socio-demographic characteristics, parity and dietary intake were collected. Complete blood counts were done. Serum ferritin, folate and cobalamin assays were performed by using DPC kits on Immulite-1000. Results: The pregnant women were categorised having mild (Hb up to 54%), moderate (Hb up to 36%), or severe (Hb up to10%) anaemia during antennal visit. They had significantly lower median (range) levels of haemoglobin 96 (40-110) g/L, ferritin 8 (3-142) µg/L, folate 15 (3-54) Î·mol/L and cobalamin 171 (111-629) ÏmolL than controls (p=<0.01). Micronutrient analysis revealed secondary pregnancy related deficiency of Iron (57%), folate (20%), combined iron and folate (19%) and cobalamin (4%) in the female. Among the risk factors, low income (OR: 7.69), multiparty (OR: 2.93), lack of iron/folate supplementation (OR 2.91) and inadequate dietary intakes (OR 2.51) were associated with anaemia. Conclusion: The pregnant anaemic women had iron (57%); folate (20%), followed by combined iron folate (19%), and cobalamin (4%) deficiency during first antenatal visit. Low income, multiparty, poor diet and lack of supplements are the main contributor in development of anaemia during pregnancy. Keywords: Anaemia, pregnancy, ferritin, cobalamin, iron, folate